Multilingual Pragmatics - Antoniou, Kyriakos (My University, 2023)
This entry reviews research on child multilingualism—the experience of regularly using more than one language from childhood—and pragmatic performance—the use and interpretation of language and nonverbal behaviors in context, so people can communicate and understand intended meanings. The entry shows that, over a broad range of pragmatic skills, multilingual children exhibit comparable to and often better performance than monolinguals. Specifically, they do not differ from monolinguals in implicature comprehension and discourse aspects that depend on pragmatics, such as narrative macrostructure, and they exhibit advantages in considering the interlocutor's communicative needs and perspective, identifying communicatively inappropriate utterances, repairing communication breakdowns, and using nonverbal pragmatic cues during communication. Moreover, multilingual children can differentiate their languages from around the age of 2 and employ the appropriate language and adjust their language use based on their interlocutor's language preference, knowledge, and choices. The entry closes by discussing four explanations about why some studies find a multilingual pragmatic advantage, while others do not.